Perancangan E-Business pada UMKM DJADIBATIK - Alphi Mukti; Pipin Yuliyanto; Putri Taqwa Prasetyaningrum (LPPM Universitas Widya Dharma, 2023)
E-Business has an impact on a company in processing internal and external data in an online system. This has an influence on running a business, especially in the MSME sector which has increased from year to year and also increasing MSME actors in Indonesia. Various sectors and types of businesses that can be developed make great potential for MSME players in starting a business that can improve the economy in society. One of the MSME sectors that deserves to be developed is batik, which is one of the heritages of the Indonesian nation that must be protected and preserved. DJADIBATIK is an MSME actor who makes batik a business by combining two cultures, namely Indonesian culture and South Korean culture, namely hanbok. These innovations and creative ideas were developed because both of them had similarities in terms of appearance and fashion style. However, along with the growth of MSMEs, it will also be followed by an increase in the number of MSME actors which will lead to competition in the same business sector. Therefore, the possibility that arises makes MSME actors need to innovate and think creatively in order to compete in a healthy manner with other MSME actors by utilizing information technology as a tool in developing business and increasing income. Observations were made in order to understand the business processes and challenges faced by DJADIBATIK, where the flow of product sales is only carried out with third party platforms and requires solutions in introducing products and expanding market segmentation. This research method uses SWOT and PESTEL analysis to find out the business strategy of DJADIBATIK SMEs. This research resulted in the design of a website-based E-business concept based on the needs of the DJADIBATIK UMKM.